2021
DOI: 10.1017/ice.2021.164
|View full text |Cite
|
Sign up to set email alerts
|

Improving antibiotic prescribing for acute bronchitis in the ambulatory setting using a multifaceted approach

Abstract: Antibiotics are frequently prescribed inappropriately for acute respiratory infections in the outpatient setting. We report the implementation of a multifaceted outpatient antimicrobial stewardship initiative resulting in a 12.3% absolute reduction of antibiotic prescribing for acute bronchitis in primary care clinics receiving active interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our overall reduction in antibiotic prescribing compares favorably to results published on similar interventions in outpatient prescribing ranging from 4.8% to 23%. 8,11,28 Previous studies have evaluated educational interventions, EHR-based interventions, or evaluation of peer-to-peer feedback individually. [8][9][10][29][30][31][32][33][34] In a recent Canadian trial, sending a single peer-comparison letter to primary-care physicians in the highest quartile of antibiotic prescribers decreased overall prescribing and prolonged-duration prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our overall reduction in antibiotic prescribing compares favorably to results published on similar interventions in outpatient prescribing ranging from 4.8% to 23%. 8,11,28 Previous studies have evaluated educational interventions, EHR-based interventions, or evaluation of peer-to-peer feedback individually. [8][9][10][29][30][31][32][33][34] In a recent Canadian trial, sending a single peer-comparison letter to primary-care physicians in the highest quartile of antibiotic prescribers decreased overall prescribing and prolonged-duration prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,28 Previous studies have evaluated educational interventions, EHR-based interventions, or evaluation of peer-to-peer feedback individually. [8][9][10][29][30][31][32][33][34] In a recent Canadian trial, sending a single peer-comparison letter to primary-care physicians in the highest quartile of antibiotic prescribers decreased overall prescribing and prolonged-duration prescribing. 28 Those letters contained recommendations and education, signed by medical leaders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding limited guidance to specifically address antimicrobial prescribing disparities, there is some evidence regarding effective practices aimed at reducing overall antimicrobial overprescribing [57][58][59]. Some of the most successful interventions have been those informed by behavioral science, such as feedback with peer comparison and accountable justification [58].…”
Section: Reducing Antimicrobial Prescribing Disparitiesmentioning
confidence: 99%
“…In another study, almost 50% of all ambulatory visits designated for acute respiratory infections (ARIs) resulted in an antibiotic prescription, and up to 30% of prescriptions were unnecessary [ 3 ]. Data from our own institution showed that outpatient prescribing for acute bronchitis (a diagnosis that almost never requires an antibiotic) varied considerably between clinics, from 40.8% to 74.5%, with a mean of 53.7% [ 4 ].…”
mentioning
confidence: 99%